Experimental investigation on an energy-efficient floor heating system with intelligent control: A case study in Chengdu, China. (August 2021) - Jiang, Caibin; Xie, Guo; Wu, Dejian; Yan, Tiantong; Chen, Siliang; Zhao, Panpan; Wu, Zhanglin; Li, Wenqiang
Abstract: The space heating system accounts for 20% 50% of building energy consumption, and may lead to energy waste due to unreasonable controls. In this study, an energy-efficient floor heating system with intelligent control was proposed to improve energy efficiency of the system. In order to validate the concept of the proposed intelligent control, an experimental system was designed and constructed in Chengdu, China. Temperature, control cycle and energy consumption were then studied under different control strategies. The result shows that a larger flow rate of supply water will result in a longer control cycle and a lower control frequency, i.e., the average control cycle at 7 L min −1 is 1.7 h during the test day, while it is 1.5 h at 5 L min −1 . Moreover, adopting water with a higher temperature and flow rate could achieve a higher efficiency of the system. The energy consumptions in case 1 (5 L min −1, 50 °C), case 2 (5 L min −1, 55 °C), case 5 (7 L min −1, 55 °C) and case 6 (7 L min −1, 60 °C) are 4746 kJ, 3534 kJ, 3093 kJ and 3028 kJ, respectively. Based on the experimental data, the supply water temperature is suggested to set lower than 60 °C considering human comfort.